Zebrafish connexin 79.8 (Gja8a): A lens connexin used as an electrical synapse in some neurons. Issue 5 (26th July 2016) - Yoshikawa, Shunichi; Vila, Alejandro; Segelken, Jasmin; Lin, Ya‐Ping; Mitchell, Cheryl K.; Nguyen, Duc; O'Brien, John
ABSTRACT: In the mammalian central nervous system, a remarkably small number of connexins is used in electrical synapses, with the majority formed from Cx36. A larger number has been detected in teleosts, with some seeming to serve restricted roles. Here, we report the discovery of a new connexin expressed in the zebrafish lens and a limited set of neurons. Zebrafish cx79.8 (gja8a), previously annotated incorrectly as cx50.5 based on a partial cDNA sequence, is a homologue of mammalian Cx50 ( Gja8 ). We examined its expression through transgenic promoter‐reporter constructs, in situ hybridization, and immunolabeling, and examined regulation of coupling in transfected HeLa cells. cx79.8 was expressed most strongly in the lens, but expression was also found in several groups of neurons in the cerebellum and related areas at the midbrain‐hindbrain boundary, in cone photoreceptors, and in neurons in the retinal inner nuclear and ganglion cell layers. Labeling in the retina with antibodies against two C‐terminal epitopes revealed numerous small punctate spots in the inner plexiform layer and along the somata of cones. Abundant gap junctions were labeled in the outer 1/3 of the lens, but were absent from the center, suggesting that the epitopes or the entire protein was absent from the center. Cx79.8 tracer coupling was strongly regulated by phosphorylation, and was extremely low in control conditions in HeLa cells due to protein phosphatase 2A activity. These properties allow coupling to be strongly restricted in situ, a frequently observed property for electrical synapses. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 548–561, 2017